Secular stagnation - Biagio Bossone (Kiel Institute for the World Economy (IfW), 2014)
This study analyzes the emergence of secular stagnation as the consequence of a rise in the preference for liquidity. Such a rise is caused by a persistent set of pessimistic expectations. This study also investigates the effectiveness of a broad range of demand-management policies in dealing with secular stagnation. To obtain these results, this study uses a model where agents derive utility from holding assets of different degrees of liquidity. In this environment, rational expectations interact with changes in market sentiment, to produce secular stagnation.
Keywords: E2; E3; E4; E5; E61; E62; E63; G11; G12; 330; helicopter money; liquidity preference; market sentiment; quantitative easing; pessimistic (optimistic) expectations; utility analysis